Data Stewardship. A new health profession for findable, accessible, interoperable and re-usable data. (20th October 2021) - Döhla, C; Dierkes, J; Zeeb, H
Abstract: Issue: In longstanding tradition of Public Health exists a tension between different stakeholders. Consensus about policies and practices is required to cope with the challenging transformation that results from digitalisation. For health systems, this means a new 'way of digital thinking', especially in research data management (RDM). In Germany, NFDI4Health, an upcoming national research data infrastructure has the potential to shape this process. Its aim is making personal and health-related research data more findable, accessible, interoperable, and re-usable (FAIR). This vision is inspired by the German Council for Scientific Information Infrastructures. Description of the problem: Health-related research data are sensitive and related to several legal restrictions. Therefore, it is particularly necessary to accompany these 'living data bodies' during their entire life cycle. Due to various opt-in or opt-out models, access and re-use may change during and after the studies. This could only be circumvented by an unlimited, irrevocable and non-purposive approval by the data donor. The consequence is a tension between individual needs and the requirements of research. Results: "Data Stewards" (DS) operate within a Task Area of NFDI4Health. In this context, they act as 'agents of change' and as 'boundary spanners' in a complex intervention; they tare individual and societal, legal and technical aspects in the field of research. A preliminary success of NFDI4Health is the integration of a DS in selected projects of a centre for clinical trials. The first milestones were to sensitize the study directors to the benefits of this intervention and to formally involve the DS. Lessons: The concept of DS embedded in NFDI4Health is innovative and could serve as a model for Public Health worldwide. Clinical trials require tailored RDM, which can be provided by DS. They have the potential to integrate individual and social aspects to make "health-related big data" FAIR. Key messages: Data Stewardship is an up-coming supporting profession for Public Health, which can help to create a "Big Picture" for more health in all policies. Data Stewardship is facing the task to handle health-related big data and to guide researchers in this field to adapt their techno-ethical work practices in the context of the digital transformation.